The attitudes of dental interns to the use of the rubber dam at Riyadh dental colleges - Bander Mohammed Al-Abdulwahhab (Saudi Endodontic Journal, 2012)
Background : The rubber dam is one of the best tools for tooth isolation and infection control in the dental field. Our aim is to evaluate the attitudes toward the use of rubber dams by dental interns in Riyadh Dental Colleges (RCsDP) and determine the barriers to their use. Materials and Methods: A self-administered questionnaire was designed and used for data collection. 150 questionnaires were distributed by hand to the dental interns of RCsDP over a period of two weeks. Information sought included the attitudes toward and difficulties for the use of the rubber dam, the time needed to apply the rubber dam, and the patients′ allergic history of the rubber dam. Respondents were asked to state their preference on a five point Likert type scale ranging from "strongly dislike" to "strongly like". The information and data of the completed questionnaires were statistically analyzed using Mann-Whitney U test and Friedman test. Results: Of 150 questionnaires distributed, 150 were completed and returned (response rate = 100%). Of those, 46.7% were males and 53.3% were females. In general; (43.3%), interns strongly liked the use of the rubber dam and the rest (46.7%) liked the use of the rubber dam. The majority of respondents liked to use rubber dam in direct restorations more than in indirect restorations and 46.7% strongly liked to use it in posterior teeth for composite restoration. Most dental interns felt that they would strongly like to use a rubber dam for endodontic treatment whether in posterior teeth (73.3%) or anterior teeth (68.7%). 66.7% of interns asked their patients if they had an allergy to latex prior to the use of the rubber dam. Child behavior (mean rank about seven) is the most important reason for not using rubber dam. The time is taken to apply the rubber dam was less than five minutes in most cases. Conclusion: Most dental interns prefer to use rubber dams in the general dental field and are enthusiastic to use it in future.